Rasio Bubuk Polisakarida Daun Cincau Hijau dan Bahan Cetak Alginat Terhadap Recovery From Deformation - Lina Lina; Titien Hary Agustantina; R Mohammad Yogiartono (Jurnal Material Kedokteran Gigi, 2012)
Alginate impression material is the most useful material. Nowadays, the material is still be imported that causes the price is relatively expensive and difficult to found in rural area. There were some efforts to modify alginate impression material by mixture Cyclea barbata L. miers leaf polysacharide powder. The impression material must fullfil the criteria of recovery from deformation. Purpose. The aim of this study was to know the ratio of Cyclea barbata L. miers leaf polysacharide powder and alginate impression material that still fullfil the criteria recovery from deformation of impression material according to the ADA. Forty-two samples is divided to six groups of mixture of Cyclea barbata L. miers leaf polysacharide powder in alginate impression material. Group A1 until A6 with the mixture of 0% (control), 40%, 42.5%, 45%, 47.5% and 50%, respectively, Cyclea barbata L. miers leaf polysacharide powder in alginate impression material. Recovery from deformation of the mixture of this impression material measured with recovery from deformation test tool with its 0.01 mm accuracy. There were significant different of Kruskal Wallis test (p<0.05), that interpreted percentage enhancement in Cyclea barbata L. miers leaf polysacharide powder in alginate impression material will increase percentage of recovery from deformation. Increasing of Cyclea barbata L. miers leaf polysacharide powder until 40% into alginate impression material produce recovery from deformation score that can fulfill the ADA criteria